KESEHATAN TELINGA SISWA SD KRISTEN EBEN HAEZAR 1 MANADO DAN SD GMIM BITUNG AMURANG KABUPATEN MINAHASA SELATAN - Pardede, Amelia M. (Universitas Sam Ratulangi, 2014)
Abstract: The hearing problem of infants and children can be hard to be detected and can caused the children to have difficulties in learning process. In Indonesia, the increasing of problem needs to have promotive, preventive, curative, and rehabilitative attempts for the people. This research uses descriptive observational method with cross-sectional design to get ear health status from students. In class V-C Eben Haezar 1 Christian Elementary School there are 31 students (17 males, 14 females). Results for students’ right ear examination, there are 8 (25,8%) with cerumen and 23 (74,2%) normal, meanwhile for the left ear, there are 8 (25,8%) with cerumen, 1 (3,2%) with outer ear wall hyperemic, 1 (3,2%) with tympanic membrane retraction and 21 (67,7%) normal. In class V GMIM Bitung Amurang Elementary School there are 18 students (11 males, 7 females). Results for students’ right ear examination, there are 8 (44,4%) with cerumen and 10 (55,6%) normal, meanwhile for the left ear, there are 11 (61,1%) with cerumen and 7 (38,9%) normal. The hearing screening from all students in both schools is normal (100%). There’s a quite big status differentiation of ear health between the two schools. Cerumen cases can be found quite a lot in both schools. Key Words: ear health, hearing screening. Abstrak: Gangguan pendengaran pada bayi dan anak dapat sulit dideteksi dan mengakibatkan anak sulit menerima pelajaran. Meningkatnya permasalahan ini di Indonesia menyebabkan diperlukan adanya upaya promotif, preventif, kuratif dan rehabilitatif terhadap masyarakat. Penelitian ini menggunakan metode deskriptif observasional secara cross-sectional untuk memperoleh status kesehatan telinga dari siswa. Di kelas V-C SD Kristen Eben Haezar 1 Manado terdapat total 31 siswa (17 laki-laki, 14 perempuan). Hasil untuk telinga kanan, ditemukan 8 siswa (25,8%) dengan serumen dan 23 (74,2%) normal, sedangkan untuk telinga kiri ditemukan 8 siswa (25,8%) dengan serumen, 1 siswa (3,2%) hiperemis dinding liang telinga luar, 1 siswa (3,2%) retraksi membran timpani, dan 21 (67,7%) normal. Di kelas V SD GMIM Bitung Amurang terdapat total 18 siswa (11 laki-laki, 7 perempuan). Hasil untuk telinga kanan, ditemukan 8 siswa (44,4%) dengan serumen dan 10 (55,6%) normal, sedangkan untuk telinga kiri ditemukan 11 siswa (61,1%) dengan serumen dan 7 (38,9%) normal. Hasil skrining pendengaran dari seluruh siswa di kedua sekolah normal (100%). Terdapat perbedaan status kesehatan telinga yang cukup besar diantara kedua sekolah. Kejadian serumen cukup banyak ditemukan di kedua sekolah. Kata kunci: kesehatan telinga, skrining pendengaran.